Effect of Calcination Temperature on Microstructural Evolution of Electrospun ZnO Fibers - Wee, Boon Siong; Kok, Kuan Ying; Nur Ubaidah, Saidin; Choo, Thye Foo; Chin, Suk Fun; Yusof, Abdullah (UR Publishers, 2018)
Development of portable or wearable devices demands for flexible, lightweight or even foldable materials for fabrication. In this respect, electrospinning offers a cost-effective, high throughput, versatile and scalable route for the production of flexible micro/nanofibers on almost all kinds of surfaces. In this work, semiconducting ZnO fibers of high aspect ratios were electrospun from organic precursor of ZnO solution. The effect of calcination temperature on the microstructures of the electrospun fibers was investigated. Simultaneous thermal analysis (STA) was used to monitor the temperature at which the organic precursor was removed to form ZnO. X-ray diffraction (XRD), on the other hand, was used to monitor the phase formations at various heating stages. Field emission scanning electron microscope (FESEM) equipped with energy dispersive spectrometry (EDX) was employed for morphological study of the ZnO produced. Continuous single phase ZnO fibers started to form at a temperature of around 460 °C and evolved through various stages of microstructural formations, from tubular-like structures to segmentation of granular structures and hierarchical structures at further increases in calcination temperatures. The ZnO fibers experienced increasing crystallinity and stoichiometry change during the heating process. When mechanically bent, the fibers were able to generate current pulses of between 0.1 to 10 nA.